CHARACTER DESIGN FOR ECO WARRIORS EDUCATIONAL GAME AS A WASTE MANAGEMENT EDUCATION MEDIUM - Tri Mustika, Nurlaela; Sigi Prameswari, Nadia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The waste problem in Indonesia requires effective education from an early age to develop environmental awareness among the younger generation. Educational games can be an effective educational medium if they have attractive and easily understood characters for children. This research aims to design characters for the Eco Warriors educational game as a waste management education medium. The research method uses literature study with a design process that includes design concept, sketching, digitalization, and character finalization. The research results consist of boy and girl character designs with environmental hero concepts that can be implemented in the development of waste management educational games as an effective and attractive educational medium for children. Keywords: Character Design, Educational Game, Waste Management